PELAKSANAAN PEMBELAJARAN E-LEARNING PRODUK KREATIF DAN KEWIRAUSAHAAN KELAS XI SMK NEGERI 5 SUKOHARJO - Yunisa Galuh Pramesti; Wiedy Murtini; Susantiningrum Susantiningrum (Universitas Sebelas Maret, 2021)
E-learning during a pandemic is the best solution to support the learning process, but what about vocational students in implementing e-learning. This study aims to determine: (1) Implementation, (2) Supporting and inhibiting factors, and (3) solutions for inhibiting factors for the e-learning process at SMK N 5 Sukoharjo. This type of research is a descriptive study with a qualitative approach. This study used purposive sampling and snowball sampling techniques with the class XI PKKwu teacher as the key informant. Data collection techniques using interviews, observation, documents, and case studies. The data validity test used source triangulation and method triangulation. Data analysis techniques with data collection, data reduction, data presentation, and drawing conclusions. The results showed that: 1) The implementation of PKKwu e-learning at SMK N 5 Sukoharjo consisted of planning, implementation, and evaluating. Planning using face to face learning lesson plans due to the lack of preparation for online learning. The implementation of PKKwu e-learning learning is carried out through the Google Classroom, Edmodo, Email, Whatsapp application, resulting in less than optimal learning of PKKwu practices, the practice of making handsanitizer and disinfectants. Evaluation is done by assessing the timeliness of collection and the correctness of answering the assignment given. 2) Supporting factors, namely the provision of credit subsidies and borrowing HP. Inhibiting factors are teacher lack of understanding of e-learning, unstable internet connection, lack of literature and official school learning media and students different economic levels. 3) The solution to these obstacles is continued coordination with parents, the use of text and audio-based learning media to minimize quotas, develop school websites, and provide training on e-learning to teachersKeywords: E-learning, Evaluation, Implementation, Inhibiting Factors, Supporting Factors, Solution